2019
DOI: 10.1186/s12879-018-3669-5
|View full text |Cite
|
Sign up to set email alerts
|

Common uropathogens and their antibiotic susceptibility pattern among diabetic patients

Abstract: BackgroundUrinary tract infection (UTIs) is a significant health problem in diabetic patients because of the multiple effects of this disease on the urinary tract and host immune system. Complicated UTIs occur most commonly in patients with abnormal genitourinary tract. Proper investigation and prompt treatment are needed to prevent morbidity and serious life threatening condition associated with UTI and diabetes co-morbidities.ObjectiveTo determine common uropathogens and antibiotic susceptibility patterns wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
68
5
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(112 citation statements)
references
References 15 publications
18
68
5
5
Order By: Relevance
“…All of the 20 studies included in this review were crosssectional by design. Most of the studies were reported from Amhara region (n = 8) [30][31][32][33][34][35][36][37] and Addis Ababa (n = 7) [38][39][40][41][42][43][44]. The remaining studies were from Oromia (n = 4) [45][46][47][48] and Southern nations (n = 1) [23].…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…All of the 20 studies included in this review were crosssectional by design. Most of the studies were reported from Amhara region (n = 8) [30][31][32][33][34][35][36][37] and Addis Ababa (n = 7) [38][39][40][41][42][43][44]. The remaining studies were from Oromia (n = 4) [45][46][47][48] and Southern nations (n = 1) [23].…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Globally, it ranges from 12% to 40.2% and in Ethiopia its prevalence is between 10.9% and 22.6%. [14][15][16][17][18] Several uropathogens have been identified in diabetic patients and the most common uropathogens isolated are Escherichia coli, Klebsiella spp., and Staphylococcus aureus. 7,9,12,18 Due to different reasons, these bacterial uropathogens showed wide-ranging resistances to different classes of antibiotics across the world.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18] Several uropathogens have been identified in diabetic patients and the most common uropathogens isolated are Escherichia coli, Klebsiella spp., and Staphylococcus aureus. 7,9,12,18 Due to different reasons, these bacterial uropathogens showed wide-ranging resistances to different classes of antibiotics across the world. 6,7, In diabetic patients, early diagnosis of UTI is essential for its proper management and to avoid the incidence of possible complications.…”
Section: Introductionmentioning
confidence: 99%
“…Woldemariam et al, 2019 reported that S. aureus 100% sensitive to nitrofurantoin, however 100% resistance to ampicillin, trimethoprim/sulphamethoxazole, and penicillin. 31 Sertaç et al, 2018 isolated multidrug resistance Staphylococcus sp. from the ocular surface of patients with diabetes.…”
Section: Discussionmentioning
confidence: 99%